Partisipasi Perempuan dalam Pemilu 2024: Komparasi Perspektif Hukum Keluarga Islam dan Feminisme - Yusuf, Helmi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This research examines women's participation in the 2024 General Election by comparing the perspectives of Islamic family law and feminist theory. In the context of the 2024 General Election, women still face various obstacles hindering their participation in the political process. This study utilizes library research methods to gather and analyze relevant literature from various sources. Findings from previous research indicate that women's representation in parliament remains low, with cultural factors, religious stigma, and political structures being major barriers. However, affirmative action policies have successfully increased the number of women in parliament. The research also reveals that Islamic family law plays a significant role in shaping women's participation through aspects such as marriage, inheritance, and roles within the family. On the other hand, feminist theory provides insights into the importance of gender equality in political participation and critiques gender bias in social, cultural, and legal structures. By integrating perspectives from Islamic family law and feminist theory, this research aims to identify gaps in understanding related to women's participation in the 2024 General Election and design holistic solutions to enhance women's participation in the political process in Indonesia.